2020
DOI: 10.1590/1980-5918.033.ao03
|View full text |Cite
|
Sign up to set email alerts
|

Center of gravity oscillations in HTLV-1-associated myelopathy/tropical spastic paraparesis

Abstract: Introduction: Postural control in individuals with HTLV-1-associated myelopathy or tropical spastic paraparesis (HAM/TSP) is usually compromised, which increases the risk of falls, makes it difficult to perform activities of daily living, and impairs the quality of life. The profile of the center of gravity oscillations in this population is unknown and may aid in clinical follow-up and research. Objective: To compare the stabilometric values between HAM/TSP and uninfected individuals and verify the existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Based on the observational studies, it is confirmed that the main problems that affect these patients involve disorders of gait 21,22,8,23 , balance 24,25,26 , pelvic floor 27,28 spasticity 29,30 and pain 10,31,32,33 . These dysfunctions affect daily life activities 5,34 and quality of life 35 .…”
Section: Discussionmentioning
confidence: 93%
“…Based on the observational studies, it is confirmed that the main problems that affect these patients involve disorders of gait 21,22,8,23 , balance 24,25,26 , pelvic floor 27,28 spasticity 29,30 and pain 10,31,32,33 . These dysfunctions affect daily life activities 5,34 and quality of life 35 .…”
Section: Discussionmentioning
confidence: 93%
“…Environmental control has been instituted as an intervention to achieve a safe home environment ( 17 – 19 ). It is common for patients with HTLV-1 to report falls and even fear of falls ( 26 ); therefore, some changes in the environment in which the patient lives are necessary.…”
Section: Discussionmentioning
confidence: 99%